Intramolecular and intermolecular enzymatic modulation of ion channels in excised membrane patches. - Bielefeldt, K (1994)
A calcium-activated potassium channel in posterior pituitary nerve terminals was modulated by phosphorylation and dephosphorylation. Nearly every patch of membrane containing this channel also contained both membrane bound protein phosphatase and membrane-bound protein kinase. By examining the statistical and kinetic nature of phosphorylation and dephosphorylation in excised patches, it was possible to evaluate two contrasting models for these enzymatic reactions. One of these models treated catalysis as an intermolecular process in which the enzyme and substrate are separate molecular species that diffuse and encounter one another during collisions. The second model treated catalysis as an intramolecular process in which the enzyme and substrate reside within a stable macromolecular complex. The study began with a Poisson analysis of the distribution of channel number in patches, and of the number of protein phosphatase-free and protein kinase-free patches. Subsequent kinetic analysis of dephosphorylation yielded an estimate of the mean number of protein phosphatase molecules per patch that was similar to the value obtained from Poisson analysis. Because these two estimates were independent predictions based on the intermolecular model, their agreement supported this model. Analysis of channel number in protein phosphatase-free patches and of the rarity of patches showing partial but incomplete rundown provided additional support for the intermolecular model over the intramolecular model. Furthermore, dephosphorylation exhibited monotonic kinetics with a rate well below the diffusion limit. Thus, several different lines of analysis support the intermolecular model for dephosphorylation, in which the protein phosphatase must encounter its substrate to effect catalysis. In contrast to the monotonic kinetics of dephosphorylation, the phosphorylation reaction exhibited sigmoidal kinetics, with a rate that depended on membrane potential. Voltage dependence is an unlikely property for a kinetic step involving encounters resulting from diffusion. Furthermore, the velocity of the phosphorylation reaction exceeded the diffusion limit, and this observation is inconsistent with the intermolecular model. Thus, both intermolecular and intramolecular enzymatic mechanisms operate in the modulation of the calcium-activated potassium channel of the posterior pituitary. These studies provide a functional characterization of the interactions between enzyme and substrate in intact patches of cell membrane.